Canine CD117-Specific Antibodies with Diverse Binding Properties Isolated from a Phage Display Library Using Cell-Based Biopanning - Mohamed A. Alfaleh; Neetika Arora; Michael Yeh; Christopher J. de Bakker; Christopher B. Howard; Philip Macpherson; Rachel E. Allavena; Xiaoli Chen; Linda Harkness; Stephen M. Mahler; Martina L. Jones (Antibodies, 2019)
CD117 (c-Kit) is a tyrosine kinase receptor that is overexpressed in multiple dog tumors. There is 100% homology between the juxtamembrane domain of human and canine CD117, and many cancer-causing mutations occur in this region in both species. Thus, CD117 is an important target for cancer treatment in dogs and for comparative oncology studies. Currently, there is no monoclonal antibody (mAb) specifically designed to target the exposed region of canine CD117, although there exist some with species cross-reactivity. We panned a naïve phage display library to isolate antibodies against recombinant CD117 on whole cells. Several mAbs were isolated and were shown to bind recombinant canine CD117 at low- to sub-nanomolar affinity. Additionally, binding to native canine CD117 was confirmed by immunohistochemistry and by flow cytometry. Competitive binding assays also identified mAbs that competed with the CD117 receptor-specific ligand, the stem cell factor (SCF). These results show the ability of our cell-based biopanning strategy to isolate a panel of antibodies that have varied characteristics when used in different binding assays. These in vitro/ex vivo assessments suggest that some of the isolated mAbs might be promising candidates for targeting overexpressed CD117 in canine cancers for different useful applications.